The Role of Cysteine in Thyroglobulin Biosynthesis - Citterio, Cintia Eliana (2021)
Thyroglobulin (Tg), the thyroid hormone precursor protein (MW ~330kDa), is synthesized under the influence of TSH in thyrocytes, where it represents ~50% of total protein synthesis. Tg structure has been shown to be stabilized by a multitude of disulfide bonds formed within the endoplasmic reticulum (ER). It has been suggested that oxidation of Tg cysteines to cystine may be critical for Tg structural maturation and secretion, although little is known about cytosolic cysteine availability for thyroidal protein synthesis. What is known is that in cystinosis, deficiency of a functional lysosomal cystine transporter (which provides, under physiological conditions, a cytosolic supply of cysteines) is genetically linked to hypothyroidism. To better understand the importance of cysteine availability, we examined PCCL3 thyrocytes exposed to Cys-limited medium. We noted that upon Cys-deprivation, there was a progressive and significant decrease of Tg mRNA, suggesting either diminished TG gene expression or enhanced TG mRNA turnover. By 24h of Cys-deprivation, Tg protein synthesis (and secretion) was dramatically decreased. The formation of disulfide pairs in the ER is through to be catalyzed by a large group of resident oxidoreductases of the ER lumen. We found that in PCCL3 cells, ER oxidoreductin-ɑ (Ero1ɑ) is positively regulated by TSH. To test the importance of Ero1ɑ for Tg folding and export, we co-expressed recombinant Tg with or without recombinant Ero1ɑ (in 293T cells) and observed that increased Ero1ɑ expression resulted in significantly increased Tg secretion. By contrast in PCCL3 cells, siRNA knockdown of Ero1ɑ resulted in decreased Tg expression and secretion. Taken together, these results suggest that both cysteine availability, and the capacity to catalyze disulfide bond formation in the ER, impact on Tg expression and its subsequent secretion leading to thyroid hormonogenesis. These findings are likely to contribute to an understanding of the pathogenesis of hypothyroidism in cystinosis; moreover, this work serves as the launch point for further studies of Tg biosynthesis in relation to intracellular glutathione and sulfur amino-acid metabolism.